O acento no português brasileiro: uma abordagem experimental - Maria Mendes Cantoni (2013)
This thesis surveys the lexical stress in Brazilian Portuguese (BP) according to a multi-representational perspective. The main goal of this study is to evaluate acoustic, articulatory and cognitive mechanisms involved in stress production and perception. In order to refine thephonological analysis with empirical evidences, a total of four experiments were designed: one regarding the production of stress and the other three regarding the perception of stress. The production experiment was designed to evaluate acoustic and articulatory properties. We recorded speech and electroglottographic signal. The results of this experiment suggest that the main acoustic property of stress in BP is duration, which can faithfully differentiate stressed syllables from pretonic, stressed syllables from posttonic as well as pretonic fromposttonic. In the series of the three perception experiments, we evaluated the interaction between stress and lexical access. The first experiment tested the parsing of ambiguous non-linguistic sequences with regard to the location of the prominence. The results from the first experiment indicate that acoustic properties influence the perception of prominence of sound patterns. The second experiment tested the influence of lexical frequency on the parsing of ambiguous linguistic sequences with regard to the location of the prominence. The third experiment tested the influence of lexical frequency on the categorical perception of stress,using stimuli generated by morphing. The second and third experiments show that the perception of stress prominence in linguistic sound patterns depends on the token frequency of the words. The findings support the idea that information on stress is lexically stored, which can successfully account for the frequency effects found in the previous perception experiments. Additionally, such findings can be supported by the that the word-level prominence involved in lexical stress can be intepreted as a result of linguistic and cognitive generalizations,which account for general tendencies in the distribution of stress in thelexicon, besides its interaction with grammar. We analyze stress as an emergent abstract pattern within a network model framework, which incorporates working principles of dynamic systems. In this analysis, we state that stress in BP might have emerged from the self-organization variables found in the stress system of Latin, as a consequence of a chain of phonological changes after vowel quantity loss. Regarding present-day BP phonological phenomena, we further argue that the multiplicity of acoustic cues in stressed syllables (trading relationship) had duration play a relevant role in contrasting reduced forms of posttonic vowels with their non-reduced counterparts.